Framing effects under different uses of performance information: an experimental study on public managers - Belardinelli, Paolo et al (2018)
Combining insights from public administration, accounting, and psychology, this article explores the microprocesses by which public managers use performance information, investigating whether the type of performance information use and the request to justify decisions affect the way in which information is processed. The study draws on data from a series of artifactual survey experiments with Italian municipal executives. Findings show that managers process information differently under ex post rather than ex ante performance information uses. More specifically, managers are more likely to be subject to framing bias under ex post than under ex ante uses of performance information. This interaction seems to be robust when subjects are asked to provide justification for their decisions. - Reproduced.
Keywords: Public management; Performance apprisal